2001
DOI: 10.1073/pnas.161294798
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence and predicted functions of the entire Sinorhizobium meliloti pSymA megaplasmid

Abstract: The symbiotic nitrogen-fixing soil bacterium Sinorhizobium meliloti contains three replicons: pSymA, pSymB, and the chromosome. We report here the complete 1,354,226-nt sequence of pSymA. In addition to a large fraction of the genes known to be specifically involved in symbiosis, pSymA contains genes likely to be involved in nitrogen and carbon metabolism, transport, stress, and resistance responses, and other functions that give S. meliloti an advantage in its specialized niche.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
227
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 281 publications
(241 citation statements)
references
References 72 publications
(62 reference statements)
7
227
0
5
Order By: Relevance
“…Although presumably involved in inducing conjugative horizontal DNA transfer, very little data currently exist regarding the functional role of the plasmid-encoded T4SS in rhizobia. Stiens et al (2006) however reported that the T4SS on pSmeSM11a from S. meliloti was not involved in mobilization of this plasmid, and S. meliloti strains containing virB operon deletions were not affected in nodulation or symbiotic nitrogen fixation (Barnett et al, 2001).…”
Section: Conjugation and Gene Transfer Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although presumably involved in inducing conjugative horizontal DNA transfer, very little data currently exist regarding the functional role of the plasmid-encoded T4SS in rhizobia. Stiens et al (2006) however reported that the T4SS on pSmeSM11a from S. meliloti was not involved in mobilization of this plasmid, and S. meliloti strains containing virB operon deletions were not affected in nodulation or symbiotic nitrogen fixation (Barnett et al, 2001).…”
Section: Conjugation and Gene Transfer Systemsmentioning
confidence: 99%
“…The repABC replicon family is required for ensuring proper segregation and efficient maintenance of low-copy DNA replicons (Ramirez-Romero et al, 2000), and has been extensively characterized and is genetically conserved in the a-proteobacteria. The repABC replicon Barnett et al, 2001), the Ti plasmids in Agrobacterium sp. strains (Li and Farrand, 2000) and the second chromosome in the animal pathogen Brucella (Paulsen et al, 2002).…”
Section: The Repabc Replicon Of Plasmid Pbtai1mentioning
confidence: 99%
See 1 more Smart Citation
“…S. meliloti has three circular replicons: a chromosome (3.65 Mb) that encodes most of the housekeeping and essential genes (10) and two megaplasmids, pSymA (1.4 Mb) and pSymB (1.7 Mb) (11). pSymA is not essential for viability but contains many of the genes required for symbiosis [nod, nif, and most fix genes (12,13)]. pSymB contains exo and dct genes required for symbiosis, as well as several genes essential for viability (14).…”
mentioning
confidence: 99%
“…1) contains both ArgE and ArgJ (Dunn, 2015), which are non-homologous isofunctional enzymes, rather than isoforms derived from a common ancestral form (Omelchenko et al, 2010). Because ArgE is the only enzyme of the predicted pathway encoded on a megaplasmid, it was suggested to have an ancillary role in ornithine production (Barnett et al, 2001). ArgJ is annotated as a bifunctional enzyme in the S. meliloti genome sequence and would thus synthesize NAG de novo as well as deacetylate NAO.…”
Section: Introductionmentioning
confidence: 99%